Władza konstytuująca jako przedmiot badań nauk prawnych - Kaleta, Krzysztof J. (Uniwersytet im. A. Mickiewicza w Poznaniu Wydział Nauk Społecznych, Instytut Filozofii UAM, 2018)
The article discusses the nature and role of constituent power in contemporary constitutional democracies. It presents the genesis of the concept of constituent power (phrased by Joseph Emmanuel Sieyès within the distinction between «pouvoir constituant» and «pouvoir constitué»), different approaches to this concept framed in the XXth century legal science by such thinkers as H. Kelsen and C. Schmitt, and finally the contemporary interpretations of this concept. The author indicates and analyses two major issues relevant to the nature and role of constituent power in the contemporary constitutional democracy. Firstly, he examines the thesis that the democratic constituent power’s activity remains normatively undetermined. The search for internal normativity that might characterise constituent power in democracy determines such practical constitutional issues as discretion of the legislator within the process of making or amending the constitution. Secondly, the author points out that analysis of the role of pouvoir constituant» in contemporary constitutionalism should not be limited to analysis of the „constitutional moment” only; the significance of constituent power should not be seen just in the framework of the one-off act of making the constitution. Constituent power should remain an active participant of constitutional discourse which induces a search for new principles ensuring balance between constituent and constituted power in constitutional democracies.
Constituent power as the subject of research in the field of legal science
Keywords: constituent power; constitutionalism; democracy; identity